Distinct hepatic myeloid and lymphoid cell repertoires are associated with susceptibility and resistance to Ascaris infection - Holland, Celia; Doherty, Derek (My University, 2021)
The soil-transmitted helminth Ascaris lumbricoides infects ~800 million people worldwide. Some people are heavily infected, harbouring many worms, whereas others are only lightly infected. The mechanisms behind this difference are unknown. We used a mouse model of hepatic resistance to Ascaris, with C57BL/6J mice as a model for heavy infection and CBA/Ca mice as a model for light infection. The mice were infected with the porcine ascarid, Ascaris suum or the human ascarid, A. lumbricoides and immune cells in their livers and spleens were enumerated using flow cytometry. Compared to uninfected C57BL/6J mice, uninfected CBA/Ca mice had higher splenic CD4+ and γδ T cell counts and lower hepatic eosinophil, Kupffer cell and B cell counts. Infection with A. suum led to expansions of eosinophils, Kupffer cells, monocytes and dendritic cells in the livers of both mouse strains and depletions of hepatic natural killer (NK) cells in CBA/Ca mice only. Infection with A. lumbricoides led to expansions of hepatic eosinophils, monocytes and dendritic cells and depletions of CD8+, αβ, NK and NK T cells in CBA/Ca mice, but not in C57BL/6J mice where only monocytes expanded. Thus, susceptibility and resistance to Ascaris infection are governed, in part, by the hepatic immune system.
PUBLISHED
Keywords: Ascaris lumbricoides; Ascaris suum; Flow cytometry; Liver; Mouse model; Resistance; Susceptibility; Immunology, Inflammation & Infection